Pepper Crop Improvement Against Cucumber Mosaic Virus (CMV): A Review - Li, Ning; Yu, Chuying; Yin, Yanxu; Gao, Shenghua; Wang, Fei; Jiao, Chunhai; Yao, Minghua (Frontiers in Plant Science, 2020)
Cucumber mosaic virus (CMV) is a prevalent virus affecting the quality and yield of pepper, resulting in yield losses of greater than 80% during severe local epidemics. Cultural practices and the heavy use of agrochemicals are the most common control measures for CMV. Sources of resistance provide a practical reference and a basis for breeding for CMV resistance. Genetic factors underlying CMV resistance have been studied and advanced breeding lines and cultivars with improved resistance have been developed by traditional breeding methods. Additionally, QTLs or genes for CMV resistance have been identified and can be utilized for marker-assisted resistance breeding. This review focuses on status and prospect of CMV against different virus strains, host resistance, and its applied genetics. With the advent of novel technologies, more useful markers and precise approaches can facilitate the progress for improving CMV resistance in Capsicum.